The Image of Mesopotamian Divine Healers : Healing Goddesses and the Legitimization of Professional asûs in the Mesopotamian Medical Marketplace - Sibbing-Plantholt, Irene (Cuneiform Monographs, 2022)
"This volume exposes one of the world's oldest medical marketplaces and the emergence of medical professionalization within it. Through an unprecedented analysis of the Mesopotamian healing goddesses as well as asûs, a diverse group of "healers", Irene Sibbing-Plantholt demonstrates that from the Middle Babylonian period onwards, the goddess Gula was employed as a divine legitimization model for scholarly, professional asûs. With this work, Sibbing-Plantholt provides a unique insight in processes of medical competition and legitimization in ancient Mesopotamia, which speak to similar processes in other societies"--